El Estado alemán durante la República de Weimar (2015)
ABSTRACT: The first half of the twentieth century, brought to the German people countless events that marked the history of a transcendental way. During the period that enclose the two world wars, there was in Germany a phase transformations in their political systems and government amended the monarchical tradition and implemented democracy, eliminating partly most benefits and powers granted under the Empire Guillermino and conservatives of a customary tradition, causing discomfort in the population and tilting to adopt extreme positions to find a solution to revitalize the German. The Weimar constitution initiated a series of reforms in terms of social rights and the welfare state, which positioned itself as a pioneer in terms of these matters, but thanks to the economic crisis, political, social and military, why pierced, never arose in an effective way.